Bankruptcy Prediction Analysis using Altman Z-Score, Springate, and Zmijewski Methods - Regita, Regita; Lubis, M Zaky Mubarak; Dewi, Novia Citra; Mohamad, Zam Zuriyati (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This study aims to predict the bankruptcy of retail companies listed on the Indonesia Stock Exchange for the period 2020-2022 using the Altman Z-Score, Springate, and Zmijewski methods, and test for significant differences between the prediction results of the three methods. The selection of retail companies is up due to sales fluctuations and downward trends during the period 2020-2022. This study uses a quantitative approach with the Kruskal-Wallis test assisted by SPSS 22 software. The research sample was selected through a purposive sampling method so that 35 companies were obtained. The results find that there were companies experiencing bankruptcy for three consecutive years according to the three methods. The data obtained is not normally distributed and heterogeneous so it uses the Kruskal-Wallis Test. The results of the Kruskal Wallis Test show a significant value, meaning that there is a significant difference between the bankruptcy prediction results of the three methods. This is due to differences in financial ratios and bankruptcy criteria used in each method. Bankruptcy Prediction; Altman Z-Score; Springate; Zmijewski; Retail Company